The Perils of Sterilization. (IMF Working Papers; Working Paper ;, 1990)
The paper argues that the sterilization of capital inflows at the start of a price-stabilization program may give rise to future pressures to discontinue the program as a result of the unduly high debt-service burden that the sterilization policy may generate.